THE MEANING OF LEISURE IN THIRD AGE (Fiep Bulletin - online, 2013)
This study of descriptive exploratory nature had as objective impounded the meaning of the leisure in the third age. The involved population is the seniors members of a group of the third age of the Center of Rehabilitation of the Senior (CRS) located in Roger's neighborhood-JP. Being selected a sample of nine subjects that accepted to participate of the study by the free and illustrious consent as the resolution N° 196/96 of the National Council of Health. They are senior avid for the life, for the knowledge, productive, different from those divulged by our materialistic society. The collection of data happened in the referred institution through the technique of semi-structured interview. To work the collected material the interpretative analysis it was used. The results evidenced unanimity in relation to the importance that the seniors attribute to the leisure in your lives, meaning for them fun, personal development, physical and mental health and amusement. This way, the practice of the leisure is life incentive and became without myth the one that is sick, unable and dependent that is labeled by the prejudice of the society of which we are part.
Keywords: Aging; leisure; social aspects